OTX015 (MK‐8628), a novel BET inhibitor, displays in vitro and in vivo antitumor effects alone and in combination with conventional therapies in glioblastoma models. Issue 9 (30th July 2016) - Berenguer‐Daizé, Caroline; Astorgues‐Xerri, Lucile; Odore, Elodie; Cayol, Mylène; Cvitkovic, Esteban; Noel, Kay; Bekradda, Mohamed; MacKenzie, Sarah; Rezai, Keyvan; Lokiec, François; Riveiro, Maria E.; Ouafik, L'Houcine
Abstract : Bromodomain and extraterminal (BET) bromodomain (BRD) proteins are epigenetic readers that bind to acetylated lysine residues on chromatin, acting as co‐activators or co‐repressors of gene expression. BRD2 and BRD4, members of the BET family, are significantly increased in glioblastoma multiforme (GBM), the most common primary adult brain cancer. OTX015 (MK‐8628), a novel BRD2/3/4 inhibitor, is under evaluation in dose‐finding studies in solid tumors, including GBM. We investigated the pharmacologic characteristics of OTX015 as a single agent and combined with targeted therapy or conventional chemotherapies in glioblastoma cell lines. OTX015 displayed higher antiproliferative effects compared to its analog JQ1, with GI50 values of approximately 0.2 µ M . In addition, C‐MYC and CDKN1A mRNA levels increased transiently after 4 h‐exposure to OTX015, while BRD2, SESN3, HEXIM‐1, HIST2H2BE, and HIST1H2BK were rapidly upregulated and sustained after 24 h. Studies in three additional GBM cell lines supported the antiproliferative effects of OTX015. In U87MG cells, OTX015 showed synergistic to additive activity when administered concomitant to or before SN38, temozolomide or everolimus. Single agent oral OTX015 significantly increased survival in mice bearing orthotopic or heterotopic U87MG xenografts. OTX015 combined simultaneously with temozolomide improved mice survival over either single agent. The passage of OTX015 across the blood–brain barrier was demonstrated with OTX015 tumor levels 7 to 15‐fold higher than in normal tissues, along with preferential binding of OTX015 to tumor tissue. The significant antitumor effects seen with OTX015 in GBM xenograft models highlight its therapeutic potential in GBM patients, alone or combined with conventional chemotherapies. Abstract : What's new? Glioblastoma multiforme (GBM) is an aggressive brain tumor, for which more‐effective therapeutic approaches are greatly needed. In the search for alternative therapies, the targeting of epigenetic processes with OTX015, an inhibitor of the epigenetic reader bromodomain (BRD) proteins BRD2, BRD3, and BRD4, has emerged as a promising strategy. Here, OTX015 demonstrated significant effects when used alone or in combination with conventional agents in glioblastoma preclinical models. Moreover, in mice, OTX015 crossed the blood–brain barrier and selectively accumulated in tumor tissues. The findings help to establish a basis for the clinical study of OTX015.